(untitled) - The World Bank in VietNam (WB) (Ha Noi, 2004)
The objective of the Second Payment System and Bank Modernization Project for Vietnam is to continue assisting the government and the banks in their efforts to modernize the financial sector through further development of the financial sector infrastructure to support economic growth, and achievement of the poverty reduction targets set out in the government's Comprehensive Poverty Reduction and Growth Strategy (CPRGS). The project has the following two components: Component 1) the main activities of this component include (i) upgrading hardware and installing new software to expand processing capability and strengthen interconnection, system, and physical security; (ii) consultant support of project implementation such as advisory services on the required legal and regulatory environment; and (iii) staff training. Component 2) focuses on the urgent need to rollout the solutions to mitigate the high operational risk of running two parallel, but completely different systems, and to enhance the system and physical security of the new facilities.
Keywords: Banks and banking,Ngân hàng và nghiệp vụ ngân hàng,Thanh toán; Vietnam,Việt Nam,Việt Nam